Fluoride removal from groundwater using chemically modified rice husk and corn cob activated carbon - Berhane Desta Gebrewold (2018)
© 2018 Informa UK Limited, trading as Taylor & Francis Group The fluoride adsorption potential of chemically modified rice husk and corn cob activated carbon was investigated in batch and column tests. The effect of pH, contact time, initial fluoride concentration and adsorbent dose on the adsorption capacity and efficiency was studied. Batch experimental results were analysed using analysis of variance. The maximum adsorption capacity of 7.9 and 5.8 mg/g and a removal efficiency of 91% and 89% were achieved in batch tests, respectively, for rice husk and corn cob activated carbon. The adsorption data and kinetic model fitted well to the Langmuir isotherm and pseudo-second-order kinetics, respectively. Fluoride adsorption was governed by both intraparticle diffusion and surface or film diffusion for both rice husk and corn cob activated carbon. Continuous tests were carried out using three columns packed with 100% rice husk activated carbon, 100% corn cob activated carbon and 50% rice husk + 50% corn cob activated carbon. The breakthrough adsorption capacities were found to be 7.9, 5.0 and 5.2 mg/g, respectively. The results were analysed using the Thomas model, which yielded adsorption capacities of 11, 8.1 and 9.4 mg/g, respectively, for the three columns investigated.